Children’s agency in reducing poverty and environmental risk : case study of Lerato house, Tshwane Leadership Foundation - Lombard, A. (Antoinette) (University of Pretoria, 2020)
Mini Dissertation (MSW (Social Development and Policy))--University of Pretoria, 2020.